Analisis Peluang Kedaulatan Negara Palestina - Fuhaidah, Ulya (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This article aims to uncover the conflict in Palestine and how the future of Palestine. The conflict in Palestine resulted in endless political chaotic even though there is a resolution of bilateral and international intervention. The future of Israeli-Palestinian peace seems just something utopian considering negotiation efforts always fail applied. The findings of research indicate that the establishment of a sovereign Palestinian state is only a dream except the following three factors manifest, first, the merging of the two political factions; Hamas and Fatah in realizing its independence; second, recognition of Israel against the Palestinian authorities so that they can coexist peacefully; and third, such as Mahmoud Ahmedi Nejad statement,